Archaeological Research of Kašučiai Fossil Fields - Nemickienė, Rėda (Archaeologia Lituana, 2016)
In the north-western part of Lithuania there are 23 known sites with preserved stone cairns and baulks – the remains of the fossil fields. First archaeological survey of these sites were organised before the Second World War, during which cairns and baulks were found. The research was initiated by Kretinga’s ethnographer, engineer Ignas Jablonskis and performed by Pranas Baleniūnas, conservator of Vytautas the Great Culture museum in Kaunas. Later, I. Jablonskis carried out research of stone cairns and baulks independently. The analysed Kašučiai fossil fields were established in a low elevation, on the left bank of Akmena river, close to the Akmena confluence with Vaineikupis stream, and preserved in the nowadays forest. I. Jablonskis discovered Kašučiai stone cairns, baulks and enclosers in 1980 and mapped some of them in 1981. One of the enclosures, which he called the enclosure No. 2, was, according to him, 110 × 40 m in size; its ends were resting on the slope of Vaineikupis stream. Inside the enclosure I. Jablonskis recorded 11 different size clearance cairns, and numerous cairns on the outer side of the stone enclosure. In 1981, I. Jablonskis investigated one of the cairns inside the enclosure. Research have shown that the cairn was built over the yellow loam, its height from the ground level reached up to 0.35 m. No artefacts, charcoal, or pottery shards were discovered inside the cairn, therefore, it has been concluded that these structures are most certainly not barrows. In 1999, Vilnius University Archaeology Department’s lecturer Algimantas Merkevičius organised an educational trip to inspect some of Kretinga district’s archaeological sites. Kašučiai fossil fields were included in the inspection. Next year, in autumn 2000, fossil fields were examined one more time along with the professor of the Tartu University Valter Lang. He confirmed that stone structures are clearance cairns and baulks that are the structures of early agriculture. In 2001, Vilnius and Tartu Universities and Kretinga museum’s archaeologists conducted investigations of the fossil fields. A part of territory was maped, and 11 baulks and 89 clearance cairns were found. The baulks were measured about 10–90 m long, 2–7 m wide and 0.15 to 0.40 m in height. Cairns’ diameter was 2–5 m, height – about 0.2–0.5 m. In 2001, 2006, 2011–2013, archaeologists from Vilnius University carried out an excavation in the territory of the site. In 2001, a cross section of a baulk was excavated. In the upper part of the baulk, four silver coins (Dutch thalers) were found. In 2006, a clearance cairn was excavated, which was located about 13 meters to the northwest from the baulk excavated in 2001. The diameter of cairn was 3.4 m and height was from 0.50 to 0.72 m, the stones were piled in two to four layers. On its outer side, large stones ranging in size from 1,05 × 0,42 × 0,40 m, 0,70 × 0,44 × 0,40 m, to 0,58 × 0,34 × 0,20 m were put, forming a sort of barrier, preventing the crumbling of smaller stones. Among the large ones, there were also smaller and medium-sized stones – about 0,25 × 0,16 × 0,10 m and 0,27 × 0,17 × 0,15 m in size. The cairn started to be built on the yellow loam. The charcoal found beneath the cairn dated back to 250–640 AD. In 2011, the excavation of Kašučiai’s fossil field was extended. A cairn located about 200 meters to the east-north-east from the excavated structures in 2001 and 2006 and about 5 meters to the west from the oval enclosure was chosen for excavation. It was 5,65 × 5,1 m in size and was mainuly built by piling mid-sized and larger stones (about 55 × 35 × 30 cm, 52 × 32 × 30 cm, 50 × 27 × 17 cm, and 50 × 33 × 16 cm). The large stones were layed in the background, the majority of them were concentrated on the edges, and inside there were smaller (about 23 × 11 × 12 cm, 17 × 17 × 13 cm etc.) and some larger stones. In the completely excavated part of the cairn, about 1,200 different-sized stones were found, piled in two to five layers that were up to 64 cm in heigh. The charcoal found beneath the cairn dated back to 620–780 AD. In 2012, two objects – a stone enclosure and the cairn inside – were explored. Some information related to the stone enclosure was clarified prior to the research. In 1980, I. Jablonskis recorded 11 cairn inside enclosures, but in 2012, 19 cairns were counted by archaeologists from Vilnius University. The size of the encloser slightly changed from 110 × 40 m to 120 × 40 m. During the excavations, a trench of the size of 24 m2 across the enclosure was investigated. It revealed that rampart was piled from medium (25 × 15 × 8 cm, 22 × 16 × 7 cm, 11 × 8 × 8 cm) and larger (47 × 30 × 20 cm, 37 × 37 × 21 cm, 26 × 34 × 16 cm) stones. On the outskirts of the baulk, there were larger 100 × 68 × 35 cm, 34 × 26 × 16 cm, 51 × 50 × 20 cm size stones placed closely next to each other. The rampart was about 4.5 m wide and its height varied from 38 cm to 51 cm in the investigated part. The inner side of it was significantly (50–63 cm) higher than the outside one. The stones of the enclosure’s rampart were stacked on a yellow loam. Inside the enclosure, a grinding stone was found. Based on analogines from other countries, the enclosure could have been used for the protection of animals or for religious rituals. The cairn inside the enclosure is dated by 14C method to 809–486 BC. In 2013, another cairn, located 2 meters southwest from the one excavated in 2012, was explored. It was dated by AMS method to 1655 ± 30 BP. Three cup marked stones were found during the survey of Kašučiai fossil field area. One of them was found about 45 meters west of the south-western edge of the enclosure. This stone is about 2,65 × 1,32 m in size, its visible height – about 0.50 m. On its upper surface, 13 cup marks were calculated. Another cup-marked stone was discovered in the southwest part of the enclosure. This is a reddish stone, about 1,35 × 1,25 m in size. Its visible height – 0.25 m. In the upper plane part there were 15 cup marks found ranging from 4.5 to 7 cm in diameter and all of them being about 1 cm deep. The third stone was discovered on the outskirts of the fossil field area, about 100 m northeast of the northern edge of the enclosure, about 50 meters south from Vaineikupis’ stream. It is a large coarse grey stone, it has a big, flat surface, the size of 2,27 × 1,55 m. The exposed part of the stone is at about 0.55 m in height. The entire upper surface of the stone was full of cup marks except for the northern part, which chipped naturally. In addition, there were some individual cup marks on the sides of the stone. The total recorded number of artificially made cup marks, whose diameters vary from 4–5.5 cm, is 169. Some of them were connected with each other. Larger cup marks were concentrated in the central and eastern parts of the stone. The two mentioned stones had a little more than 10 cup marks. For this type of objects, such number of cup marks was average and typical of Scandinavia, Germany, and Estonia. In these countries, many stone cup marks are being found in the fossil field areas. Archaeologists have given a variety of interpretations to explain the function of these objects. However, the majority of them believe that the stones with cup marks are associated with soil fertility rituals. Typically, these objects date back to the first millenium BC. Kašučiai case possibly confirms the hypothesis that stones with cup marks are related to the agricultural rituals. In addition to the archaeological investigations carried out, there were also pollen analysis and geochemical soil investigations done, which also shows the anthropogenic impact on the studied area. Thus, based on the obtained results, we can hypothesise that the stone cairns located inside the encloser are the earliest ones. They date back to the late Bronze – Roman Iron Age. Clearance cairns found in the rest of the territory belong to the later, Migration Period, but may be of the earlier cultivation period. The wide chronological range and the large prevalence of stone cairns across the territory certainly sugest long-term use of Kašučiai fossil fields.
Keywords: Kašučiai fossil fields; cairn; baulk; enclosure; cup marked stone